Advances in the Gel Preparation and Its Affecting Factors of Soybean Protein - Xiuqing ZHU; Xiaoqi DENG; Ying ZHU; Xiquan WANG; Yuling LI; Xiaoyu XIA (Shipin gongye ke-ji, 2023)
As one of the important food crops in China, soybean has a high nutritional value. Gelation is of great interest as an important functional property of soybean isolate proteins. Soy protein is mostly used as an encapsulation carrier for a variety of complexes such as water molecules, sugars, lipids and unstable small molecule active substances in products, but the natural gel products of soy protein have problems such as loose structure and low yield, which greatly limits the application and development of its gel products. In this paper, the mechanism of gel formation from soy protein isolates is analyzed, and the intrinsic influencing factors such as soy protein conformation and composition, polysaccharide and lipid interactions and ionic strength, as well as the influence of external factors such as physical, chemical and biological factors on gel formation are discussed in depth and systematically analysed, with a view to providing a theoretical basis for the processing and utilization of soy protein gel products in the future.